Distribution of Chromium, Manganese and Cobalt in the Bottom Sediment of Pahang River-Estuary, Pahang, Malaysia - Yunus, Kamaruzzaman; Abdurahman, Siti Waznah; Md Suhaimi, Mohd Zahir; Ong, Meng Chuan; Saad, Shahbudin; Khan Chowdhury, Ahmed Jalal; Zabri, Rina Sharlinda; Muhamad Tajudin, Nur Shuhada; John, Akbar; Bidai, Joseph; Al-Barwani, Said Mohd; Goddard, J Stephen (Asian Network for Scientific Information, 2010)
Bottom sediments from 62 stations at Pahang river-estuary were analyzed for the concentrations of Chromium (Cr), Manganese (Mn) and Cobalt (Co). Heavy metal concentrations were analyzed by using an Inductively Coupled Plasma Mass Spectrometry (ICP-MS). The average dry weight concentrations of Cr, Mn and Co were 62.80±20.04, 416.21±127.41 and 7.93±3.25 μg g-1, respectively. The observed concentrations of the studied metals were significantly higher near the estuary and declining as the sampling points were further away from the estuary. The Enrichment Factors (EFs) were calculated and all elements showed metal contamination was predominantly of terrigenous in origin.